2017
DOI: 10.1136/heartjnl-2017-311774
|View full text |Cite
|
Sign up to set email alerts
|

Management of Kawasaki disease in adults

Abstract: Kawasaki disease is the most common childhood vasculitis in the USA and the most common cause of acquired cardiac disease in children in developed countries. Since the vast majority of Kawasaki disease initially presents at <5 years of age, many adult cardiologists are unfamiliar with the pathophysiology of this disease. This vasculitis has a predilection for coronary arteries with a high complication rate across the lifespan for those with medium to large coronary artery aneurysms. An inflammatory cascade pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 46 publications
0
33
0
6
Order By: Relevance
“…With the 1st suspected case reported in 1967 (Kawasaki, 2002), KD was identified as an acute pediatric systemic vasculitis with clinical symptoms such as sustained fever, oral mucosal lesions, pleural rash, swollen cervical lymph nodes, conjunctival hyperemia, severe swelling of hand and foot with skin peeling on fingertips. One of the most serious sequelae of KD is the inflammation of the heart arteries which lead to the formation of aneurysm and coronary artery lesions (CALs) (Denby et al, 2017). Besides, KD was reported to affect many different organ systems including blood vessels, mucous membranes, skins and lymph nodes (Kuwabara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the 1st suspected case reported in 1967 (Kawasaki, 2002), KD was identified as an acute pediatric systemic vasculitis with clinical symptoms such as sustained fever, oral mucosal lesions, pleural rash, swollen cervical lymph nodes, conjunctival hyperemia, severe swelling of hand and foot with skin peeling on fingertips. One of the most serious sequelae of KD is the inflammation of the heart arteries which lead to the formation of aneurysm and coronary artery lesions (CALs) (Denby et al, 2017). Besides, KD was reported to affect many different organ systems including blood vessels, mucous membranes, skins and lymph nodes (Kuwabara et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of coronary events in people with a history of KD remains unclear. Japanese guidelines and AHA guidelines recommend several management options for each coronary sequela, but it is not known how frequently ischemic heart disease occurs among people with a history of KD‐related cardiac sequelae . Thus, the CIBC, which showed that one in 3,000 males and one in 6,000 females born in 2007 developed KD‐related cardiac sequela, is useful for considering their management to prevent ischemic heart disease in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with KD occasionally develop cardiac sequelae, increasing the risk of subsequent ischemic heart disease in adulthood . Investigating the proportion of individuals with KD with cardiac sequelae in the general population, especially by birth cohort, i.e.…”
mentioning
confidence: 99%
“…It can sometimes be seen in adults and presents with lymphadenopathy, hepatitis, arthralgia, constitutional symptoms, and coronary artery involvement. A long-term follow-up with a cardiologist is recommended to assess regularly for the onset of complications such as persistent coronary aneurysms and accelerated atherosclerosis [26,27]. Mimics of MVV are presented in Table 3. 3.1.…”
Section: Medium-vessel Vasculitis Mimicsmentioning
confidence: 99%